Mechanical Bonding of Aluminum Hybrid Alloy Systems through High‐Pressure Torsion. Issue 1 (2nd August 2019) - Kawasaki, Megumi; Jung, Seon Ho; Park, Jeong-Min; Lee, Jongsup; Jang, Jae-il; Han, Jae-Kyung
Abstract : The present study demonstrates an innovative approach of utilizing high‐pressure torsion (HPT) processing for the mechanical bonding of dissimilar metals during the microstructural refinement process. This processing approach has been developed recently for introducing unique alloy systems with improving physical and mechanical properties. Accordingly, the present study focuses specifically on the microstructural evolution and development in micro‐mechanical responses in the mechanically bonded Al‐Mg and Al‐Cu hybrid alloy systems when synthesized by HPT processing for very high number of turns up to 60 under 6.0 GPa at room temperature. The microstructural and hardness evaluations confirm the capability of the HPT procedure for the formation of heterostructures with extreme hardness at the disk peripheries and with low hardness at the disk centers in these processed alloy systems. Nanoindentation measurements demonstrate that both hybrid alloy systems exhibit excellent plasticity at the disk edges, where the hardness is the highest. There is a considerable potential for applying the solid‐state reaction through the HPT process for the bonding of dissimilar metals as a manufacturing technique and for the development of hybrid alloy systems. Abstract : An innovative metal bonding approach is demonstrated by utilizing the conventional high‐pressure torsion process at room temperature. The evolution of macro‐ and micro‐mechanical responses is evaluated in the synthesized alloy systems of Al‐Mg and Al‐Cu with increasing numbers of HPT turns. This study provides a significant contribution to developments in the current bonding and joining manufacturing techniques.